“Third-State connections” in the proposal for an EU regulation on parenthood: more than a regime of circulation of the status between Member States? - Danieli, Diletta (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Starting from the main features of the scope of application of the proposal for an EU regulation on parenthood, the paper follows a cross-cutting assessment with a view to determining whether, and how, the proposed instrument considers the elements of connection that a parent-child relationship may have, in a given case, with States that are not members of the EU. Some final considerations are then proposed on the possible policy grounds underlying the analysed provisions.